2004
DOI: 10.1161/01.hyp.0000111136.86976.26
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Causal Role of the Renin-Angiotensin System in Vascular Dysfunction Associated With Insulin Resistance

Abstract: Abstract-Excess production of superoxide anion in response to angiotensin II plays a central role in the transduction of signal molecules and the regulation of vascular tone. We examined the ability of insulin resistance to stimulate superoxide anion production and investigated the identity of the oxidases responsible for its production. Rats were fed diets containing 60% fructose (fructose-fed rats) or 60% starch (control rats) for 8 weeks. In aortic homogenates from fructose-fed rats, the superoxide anion ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
135
4
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 57 publications
7
135
4
4
Order By: Relevance
“…On the other hand, angiotensin inhibits the meta-bolic actions of insulin via the phosphatidylinositol 3-kinase pathway 2) , resulting in insulin resistance. Angiotensin type 1 receptor (AT1R) blockers (ARBs) and angiotensin-converting enzyme inhibitors, which function as antihypertensive agents, have been reported to prevent atherosclerosis in a study using monkeys 3) , improve insulin resistance 4) , and induce a favorable lipid profile 5,6) . Besides their metabolic effect on insulin signaling, telmisartan 7,8) and irbesartan 7) , two ARBs, have been found to activate peroxisome proliferator-activated receptor (PPAR ) in cells derived from rodents and this is independent of their AT1R blocking actions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, angiotensin inhibits the meta-bolic actions of insulin via the phosphatidylinositol 3-kinase pathway 2) , resulting in insulin resistance. Angiotensin type 1 receptor (AT1R) blockers (ARBs) and angiotensin-converting enzyme inhibitors, which function as antihypertensive agents, have been reported to prevent atherosclerosis in a study using monkeys 3) , improve insulin resistance 4) , and induce a favorable lipid profile 5,6) . Besides their metabolic effect on insulin signaling, telmisartan 7,8) and irbesartan 7) , two ARBs, have been found to activate peroxisome proliferator-activated receptor (PPAR ) in cells derived from rodents and this is independent of their AT1R blocking actions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have pointed out active involvement of renin-angiotensin system (RAS) in cardiovascular disorders and insulin resistance (5,6). RAS further splits in two, as follows: angiotensin (ANG) II/ACE1 and ANG-(1-7)/ACE2 axis.…”
mentioning
confidence: 99%
“…Dzau VJ, Safar ME, amongst many other elite scientists, have shown that hypertension, dyslipidemia, and insulin resistance are associated with renin-angiotensin system activation and generation of large amounts of angiotensin II (Dzau & Safar, 1988;Shinozaki et al, 2004).…”
Section: Management Of Reduced High-density Lipoprotein Cholesterol (mentioning
confidence: 99%